Quercetin-Containing Extract from Clove Syzygium aromaticum L. Endophytic Bacteria, Fictibacillus phosphorivorans P1U2, Exhibits Antimutagenic Activity in Yeast Saccharomyces cerevisiae - Nadila Fany Ashafani; Rika Indri Astuti; Sri Listiyowati; Irmanida Batubara (HAYATI Journal of Biosciences, 2023)
Metabolites from clove (Syzygium aromaticum L.) have been extensively studied for various pharmacological uses, including quercetin. Endophytic bacteria isolated from plant tissues can produce similar secondary metabolites as their host plants. However, little is known about the antioxidant activity of the endophytic bacterial extract from clove leaves. Amongst the potential bacterial groups, the genera of Bacillus have been widely studied as a source of antioxidants. Thus, this study, we examined the potential antioxidant properties of Bacillus sp., isolated from clove leaves. We have successfully isolated ten endophytic bacteria, of which only one isolate (P1U2) was found non-pathogenic based on a hemolytic assay. Based on the 16S rRNA sequence, P1U2 shared the highest similarity to Fictibacillus phosphorivorans. The extract of extracellular metabolites of P1U2 contains quercetin compounds, based on LC-MS analysis. The results of the antioxidant activity test using the DPPH assay showed that the P1U2 extract had an IC50 value of 161 mg/ml. The supplementation of the extract on culture media reduced the ability of S. cerevisiae to decolorize mutagen malachite green and increased cell viability. Furthermore, the addition of 161 ppm extract was able to counteract UV mutagens effects of UV exposure and toxicity of malachite green, significantly increasing the growth of S. cerevisiae. Suggesting the bioactivity of the extract in combating mutagens. To the best of our knowledge, this is the first study to report a quercetin-rich extract derived from endophytic bacteria, F. phosphorivorans. Thus, further study is required to optimize the synthesis of quercetin from isolate P1U2.